Effect of Erythropoietin on Postresuscitation Renal Function in a Swine Model of Ventricular Fibrillation. (25th October 2016) - Pantazopoulos, Charalampos; Iacovidou, Nicoletta; Kouskouni, Evangelia; Pliatsika, Paraskevi; Papalois, Apostolos; Kaparos, Georgios; Barouxis, Dimitrios; Vasileiou, Panagiotis; Lelovas, Pavlos; Kotsilianou, Olympia; Pantazopoulos, Ioannis; Gkiokas, Georgios; et al.
Abstract : Purpose . To investigate the effect of EPO administration on postresuscitation renal function. Methods . Twenty-four female Landrace/Large-White piglets aged 10–15 weeks with average weight of 19 ± 2  kg were randomly assigned to 2 different groups of 12 subjects each. After the end of an 8-minute ventricular fibrillation, the control group (Group C) received saline as placebo, whereas the EPO group (Group E) received EPO 5000 U/kg. The animals were resuscitated according to the 2010 European Resuscitation Council Guidelines for Resuscitation. Results . Five animals (41.67%) from Group C and 11 animals (91.67%) from Group E achieved ROSC (p = 0.027 ). Eight animals (66.67%, 5 surviving and 3 nonsurviving) from Group C suffered severe kidney damage or AKI compared to animals from Group E, in which none of the swine had evidence of severe kidney damage or AKI (p = 0.001 ). There was a statistically significant difference in all tested biochemical markers between the two groups, as well as a positive correlation of creatinine with NGAL, L-FABP, and IL-18 (summed mean values' p = 0.049, 0.01, and 0.004, resp.). Conclusions . Administration of EPO protected swine from postresuscitation acute kidney injury.